Understanding the Legal Implications of Regulatory Transfers: A Post-Decision Analysis of MK No. 27/PUU-IX/2011 under the Omnibus Law Framework - Mariza, Siska; Santoso, Imam Budi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The revocation of Articles 64 and 65 of the Labour Law and the amendment of Article 66 of the Labour Law concerning the provisions limiting outsourcing or outsourcing in the UUCK have also caused conflict among workers. This conflict stems, among other things, from the perception that outsourcing in the Ciptaker Law is exploitative and marginalises the human side of workers because it expands the scope of outsourcing. The purpose of this study is to examine the problem of outsourcing provisions in the Ciptaker Law that give companies the flexibility to use subcontracted labour, which in this case can trigger the occurrence of modern slavery, thus threatening the security and vulnerability of permanent job creation. security and rights. This review is based on laws and various regulations regarding the legality and form of outsourcing. In this research the normative jurisprudence method is used in conjunction with normative jurisprudence. The results of the research show that the abolition and modification of the UUCK subcontracting regulations have caused many conflicts that are detrimental to workers/employees. The disadvantages received by outsourced workers include that outsourced workers do not have a clear career path and do not have the right to become permanent employees. They receive lower salaries, do not have the right to receive benefits, do not have the same protection as permanent employees and do not have the right to receive the same benefits as permanent employees.